Digital literacy in higher education teachers - short review - Ribeiro, Maria Isabel (2022)
Nowadays, Information and Communication Technologies (ICT) are fundamental in all areas of study of the higher education system, playing a central role in learning and teaching. The proper use of ICT, in conjunction with modern teaching practices, can increase the efficiency of teaching and learning processes in higher education. Higher education acts on three dimensions, namely, the integration and use of new educational technologies in higher education; European convergence and the application of ICT; and innovation and education necessary to bridge the gap between higher education institutions and teachers, both socially and professionally. The main objective of this study was to investigate the current status about digital competence of higher education teachers. This short review was based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement. From the definition of the objectives, the Scopus database was screened. The searches were performed in November 2021, using the combination of the keywords “ICT”, “skills”, “digital”, “literacy”, “education”, “higher” and “teachers”, as well as their synonyms. Initially, 37 publications were identified. At this stage, the following screening criterion was considered: sample constituted by higher education teachers (public and private). To identify publications that included only higher education teachers, abstracts and, when necessary, the entire text were selected. Afterwards, 26 studies were removed, leading to 11 eligible publications. The results indicate that, although digital competences are part of the current professional profile of higher education teachers and the transition to digital education is an inevitable trend in modern education, higher education institutions must continue to support teachers so that they can develop their skills. This way, online teaching and other forms of teaching and learning that have emerged from the digital age can be used to explore the opportunities presented by technology in order to improve the quality of teaching and learning. Given the almost universal use of e-learning in higher education, the literature highlights the importance of digital skills for higher education teachers who can act as teachers of the future, better preparing students for the labour market and creating a new generation that can participate effectively in online communities and other e-governance devices that promote democracy, equity and social justice. This literature review will serve as the basis for the preparation of an empirical research involving teachers from five higher education schools from Instituto Politécnico de Bragança, a higher education institution located in the inland North of Portugal (Agriculture, Education, Technology and Management, Administration and Tourism, and Health). With the development of this future research, which will aim to analyse the level of digital skills, attitudes, the difficulty of using technological tools in an educational context, it is intended to collect information that can be used to define strategies to improve digital skills among teachers from higher education.